A Polymorphism in the Chitotriosidase Gene Associated with Risk of Mycetoma Due to Madurella mycetomatis Mycetoma--A Retrospective Study. - Patricia E B Verwer; Charlotte C Notenboom; Kimberly Eadie; Ahmed H Fahal; Henri A Verbrugh; Wendy W J van de Sande (Public Library of Science (PLoS), 2015)
BACKGROUND:Madurella mycetomatis is the most prevalent causative agent of eumycetoma in Sudan, an infection characterized by the formation of grains. Many patients are exposed to the causative agent, however only a small number develop infection. M. mycetomatis contains chitin in its cell wall, which can trigger the human immune system. Polymorphisms in the genes encoding for the chitin-degrading enzymes chitotriosidase and AMCase were described, resulting in altered chitinase activity. We investigated the association between 4 of these polymorphisms and the incidence of M. mycetomatis mycetoma in a Sudanese population. METHODOLOGY:Polymorphisms studied in 112 eumycetoma patients and 103 matched controls included a 24-bp insertion in the chitotriosidase gene (rs3831317), resulting in impaired chitinase activity and single nucleotide polymorphism (SNP) in the AMCase gene (rs61756687), resulting in decreased AMCase activity. Also, a SNP (rs41282492) and a 10-bp insertion in the 5'UTR region of the AMCase gene (rs143789088) were studied, both resulting in increased AMCase activity. DNA was isolated from blood and genotypes were determined using PCR-RFLP. PRINCIPAL FINDINGS:Histological staining proved the presence of chitin in the fungal grain. The polymorphism resulting in decreased chitotriosidase activity was associated with increased odds of eumycetoma (odds ratio 2.9; p = 0.004). No association was found for the polymorphisms in the genes for AMCase (all p>0.05). CONCLUSION:Decreased chitotriosidase activity was associated with increased risk of M. mycetomatis mycetoma.